1998
DOI: 10.1007/pl00009717
|View full text |Cite
|
Sign up to set email alerts
|

Shoot dynamics and architecture of saplings in Fagus crenata across its geographical range

Abstract: AbstractmRelationships between leaf or shoot size, number, and arrangement in response to light were investigated to test the hypothesis that these characteristics are linked. In order to test this hypothesis, the divergence in allometry and shoot dynamics in saplings of Japanese beech (Fagus crenata) obtained from four populations and having different leaf sizes were examined in a nursery under both full sun and shade conditions. Trees with different leaf sizes also showed large differences in canopy structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
2
21
0
2
Order By: Relevance
“…the northeast populations across the species' geographic range (Hagiwara 1977). A common garden study of F. crenata saplings confirmed this clinal variation in leaf size and, moreover, revealed that saplings with large leaves have narrow, vertically extended crowns, while those with small leaves have flat, horizontally extended crowns, due to their different shoot dynamics (Hiura 1998). Fujii et al (2002) examined chloroplast DNA (cpDNA) variation in F. crenata populations across the species' range, and found a strong geographic structure among 13 haplotypes, with a subdivision into two major lineages: one mainly distributed along the Sea of Japan side and the other chiefly along the Pacific side of the Japanese Islands.…”
Section: Introductionsupporting
confidence: 51%
“…the northeast populations across the species' geographic range (Hagiwara 1977). A common garden study of F. crenata saplings confirmed this clinal variation in leaf size and, moreover, revealed that saplings with large leaves have narrow, vertically extended crowns, while those with small leaves have flat, horizontally extended crowns, due to their different shoot dynamics (Hiura 1998). Fujii et al (2002) examined chloroplast DNA (cpDNA) variation in F. crenata populations across the species' range, and found a strong geographic structure among 13 haplotypes, with a subdivision into two major lineages: one mainly distributed along the Sea of Japan side and the other chiefly along the Pacific side of the Japanese Islands.…”
Section: Introductionsupporting
confidence: 51%
“…Several studies have showed trade-offs between the rate of growth and defense (Coley 1983, Shure andWilson 1993). Hiura (1998) suggested physiological gaps between a leaf's characteristics and whole plant growth. Hiura (1998) suggested physiological gaps between a leaf's characteristics and whole plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Short shoots of the former will therefore have a longer stem lifespan than short current-year shoots of the latter. The difference in stem life-span (Millington andChaney 1973, Addicott 1982, Bilbrough andRichards 199l, Ginocchio and Montenegro 1992, Buck-Sorlin and Bell 1998) among these species will presumably be revealed by studying shoot dynamics (e.g., Maillette 1982, Chester and McGraw 1983, Jones and Harper 1987, Hiura 1998, Stoll and Schmid 1998.…”
Section: Implications Of the Type Of Shoot Differentiation For Foliagmentioning
confidence: 99%